ОБРАЗ ВРЕМЕНИ И ХУДОЖЕСТВЕННАЯ ИДЕЯ В РАБОТАХ Ш. ХОЛМИРЗАЕВА - Хамидуллаева, Г.А. (SCIENCE and SOCIETY, 2025)
The article analyzes Shukur Holmirzaev's novella «Who Hasn’t Turned Eighteen Yet?», which explores timeless issues such as loneliness, isolation, and the inner struggle of the individual. The emphasis is placed on the importance of literature in educating the youth and preserving cultural heritage through essayism, which is highlighted as a defining feature of the work. The relevance of the theme across different eras and its impact on the perception of human identity in modern society is also discussed.
Keywords: Shukur Holmirzaev; the problem of the era; essayism; loneliness and isolation